Diastereoselective peroxidation of derivatives of Baylis–Hillman adducts - Zuckerman, Dylan S. (Tetrahedron, 2019)
Cyclic derivatives of Baylis–Hillman adducts were synthesized. Cobalt-catalyzed peroxidation of these cyclic lactones afforded silyl peroxides in diastereomeric ratios ranging from 91:9 to 97:3.